The effects of dipeptidyl peptidase-4 inhibitors on cardiac structure and function using cardiac magnetic resonance: a meta-analysis of clinical studies - Wang, Haipeng; Guo, Siyi; Gu, Shuo; Li, Chunyu; Wang, Fei; Zhao, Junyu (Frontiers in Endocrinology, 2024)
Objective: The aim of the study was to evaluate the effect of dipeptidyl peptidase-4 inhibitors (DPP4i) on cardiac structure and function by cardiac magnetic resonance (CMR).Research Methods & Procedures: Database including PubMed, Cochrane library, Embase and SinoMed for clinical studies of DPP4i on cardiac structure and function by CMR were searched. Two authors extracted the data and evaluated study quality independently. Mean difference (MD) or standardized MD and 95% confidence intervals (CI) were used for continuous variables. Review Manager 5.3 was used to performed the analysis.Results: Ten references (nine studies) were included in this meta-analysis. Most of the studies were assessed as well quality by the assessment of methodological quality. For clinical control studies, the merged MD values of △LVEF by fixed-effect model and the pooled effect size in favor of DPP4i was 1.55 (95% CI 0.35 to 2.74, P=0.01). Compared with positive control drugs, DPP4i can significantly improve the LVEF (MD=4.69, 95%CI=2.70 to 6.69), but no such change compared to placebo (MD=-0.20, 95%CI=-1.69 to 1.29). For single-arm studies and partial clinical control studies that reported LVEF values before and after DPP4i treatment, random-effect model was used to combine effect size due to a large heterogeneity (Chi 2 =11.26, P=0.02, I 2 = 64%), and the pooled effect size in favor of DPP4i was 2.31 (95% CI 0.01 to 4.62, P=0.05). DPP4i significantly increased the Peak filling rate (PFR) without heterogeneity when the effect sizes of two single-arm studies were combined (MD=31.98, 95% CI 13.69 to 50.27, P=0.0006; heterogeneity test: Chi 2 =0.56, P=0.46, I 2 =0%).Conclusions: In summary, a possible benefit of DPP4i in cardiac function (as measured by CMR) was found, both including ventricular systolic function and diastolic function.